The Application of Problem Based Instruction (PBI) Model with Geogebra Application to Improve Student Learning Outcomes and Activities - Hasanatum Munawaroh (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
Learning is the main activity of the education process. The researcher observed in class VIII MTs. SA Nurul Qona'ah Mumbulsari and obtained data about 46.2% shows the value of students ? 70. This study aims to determine the Improvement of Learning Outcomes and Activities of Students in studying the function graph material by applying the Problem Based Intruction (PBI) learning model, the type of research that used is class action research (CAR). The procedure used is a cycle model. Based on the results of the study, the percentage of student learning activities in the first cycle was 83.20% and the second cycle was 88%. While the daily test results of students in the first cycle obtained an average value of 73.1% while in the second cycle it was 85.03%. This proves that learning outcomes and student activities can increase with the implementation of the Problem Based Intrusion (PBI) learning model with geogebra applications. For certain subjects, this model is used to avoid saturation in learning activities. Keywords: problem based instruction, geogebra, learning outcomes, student activity